Bibliometric Analysis of Funding Aspect in the Domain of Marine Protected Area - Roby Fadillah; Yonvitner; Luky Adrianto; Hefni Effendi (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2025)
This paper conducts a comprehensive literature review on the aspect of funding in the management of Marine Protected Areas (MPAs) using bibliometric analysis through the VOSviewer software. Indonesia, as a country with high biodiversity, heavily relies on marine ecosystems, making effective MPA management reliant on adequate funding for monitoring, surveillance, and habitat rehabilitation. International publication data were collected from Scopus (2000-2024) using the keywords "Marine + protected + area + finance", yielding 47 articles analyzed to map research trends and relationships among factors. The analysis results show an increase in studies since 2017, focusing on MPA management, sustainability, environmental protection, biodiversity, and financial aspects. Network visualization reveals strong interconnections between funding, governance, and community participation in MPA management. In conclusion, funding is a critical aspect that still requires further development through additional research.